ANALISIS EFISIENSI DAN EFEKTIVITAS PENERIMAAN PENDAPATAN ASLI DAERAH DI MASA PANDEMI COVID-19 PADA BADAN PENDAPATAN DAN ASET DAERAH PROVINSI NUSA TENGGARA TIMUR - Peter Rinto Rivaldo Goa; Hapsa Usman; Munawar Munawar (P3M- Politeknik Negeri Kupang, 2021)
The results of the financial statements of the Provincial Government, especially during the COVID-19 Pandemic 2020, it shows that the realization of the Regional Original Revenue budget has not reached the specified target. Realization of Original Regional Revenue is still fluctuating, namely it is still up and down in the Regional Government Budget of the NTT Province, so it is said to be still unstable. The data analysis technique is descriptive quantitative. The types of data used are qualitative data and quantitative data. Sources of data used are primary data and secondary data. The data was collected by means of observation, interviews, literature study and documentation which will be analyzed using the PAD efficiency ratio and the PAD effectiveness ratio. The results of the study show that the efficiency level of Regional Original Revenue before the COVID-19 Pandemic, namely in 2018 and 2019 was classified as very efficient. In 2018 it was 1.56%, in 2019 it was 1.66%. While the efficiency level of Regional Original Revenue during the COVID-19 Pandemic, namely in 2020 is classified as very efficient with a percentage of 1.71%. The level of effectiveness of local revenue receipts in the period before the COVID-19 pandemic was classified as very effective. In 2018 the percentage was 100.44% and in 2019 the percentage was 97.95%. Meanwhile, during the COVID-19 pandemic, in 2020 the level of effectiveness was classified as less effective with a percentage of 79.59%. This is due to the weakening of economic factors and the large number of tax arrears